The place of the National Police of Ukraine in the system of subjects for prevention and counteraction to bullying - O. V. Dzhafarova; О. А. Morhunov; D. A. Sorochan (Law and Safety)
One of the areas of ensuring the rights of the child is to create a favorable environment for education, training, development and an effective system to ensure the realization of his or her rights. Bullying has become a common way of self-affirmation in schools. Sometimes participants in the educational process violate not only the norms of morality, but also the legal norms, for the violation of which there is legal liability. The aim is to study the place of the National Police of Ukraine in the system of subjects for prevention and counteraction to bullying and promising areas for improving the order of interaction between them. The scientific novelty of the study is that on the basis of a comprehensive analysis of national legislation, departmental bylaws and research in various fields on this topic, it was identified a system of subjects to prevent and combat bullying and promising areas for improving the interaction of the National Police with other entities in this area.. It was found that the bodies of the National Police of Ukraine are perhaps the most important state body, whose officials are obliged to consider and resolve cases of administrative offenses in most areas of public relations in the country. It is determined that the main tasks for preventing and combating bullying are prescribed only for educational institutions, and not for the entire list of subjects of response (prevention and counteraction), which negatively affects the effectiveness of these activities. This proves once again the need to adopt a separate piece of legislation to prevent and combat bullying in Ukraine. It is emphasized that the issue of the system of subjects for prevention and counteraction to bullying in Ukraine is ambiguous. On the one hand, it is quite broad, on the other hand, there is no clear legislative regulation on this issue. Therefore, there is a big problem in the order of interaction of the subjects for prevention and counteraction to bullying with each other, which negatively affects the common goals and objectives of this activity. It was found that the prevention and counteraction of bullying in the realities of today’s Ukrainian society is a priority in the fight against this phenomenon, the level of which is constantly growing. It is established that the main obstacles in the effective interaction of the National Police with various actors to prevent and combat bullying are the private and public aspect of this phenomenon, the intersectoral nature of this activity and the large number of organizational links. It is determined that the main problem is the lack of legislation that clearly establishes the list of subjects to prevent and combat bullying in Ukraine. It is emphasized that the specific focus of the juvenile prevention units activities, related to work with children (victims and child abusers), determines the unique interpretation of the functions performed by these units in this area.